Adsorption of Reactive Orange 16 onto Gracilaria Species a Marine Alga - RAJHA AMARNATH, D.; PADMESH, T.V.N. (Asian Journal of Chemistry, 2010)
Decolourization of reactive orange by Gracilaria verrucosa was evaluated under several parameter conditions. The decolourization method consisted of adding 0.2 g marine alga biomass in 50 mL of solution containing dye of different concentrations together in a rotary shaker. The decolourization profile was highly dependent upon the initial pH concentration, the adsorbent dosage and the temperature of the dye solution. Marine alga biomass exhibited higher uptakes at pH 4 of all concentrations examined. The high uptakes values at 0.2 g/50 mL was observed and then decreased for the further increase in dosage. As the temperature increased the uptake of dye increases up to room temperature and the uptake decreases with further increase in temperature. Adsorption isotherms have been correctly represented by Langmuir, Freundlich isotherm model.